Evaluation Of The Emergency Nursing Master’s Program: A Qualitative Approach - Duman, Ayfer Şahin; Mıdık, Özlem (Hemşirelikte Araştırma Geliştirme Derneği, 2025)
Objective: The aim of the study was to evaluate the Emergency Nursing Postgraduate Program of a university in Turkey in line with the opinions of students and nurse educators. Material and Method: This study is a qualitative program evaluation study using the Eisner Educational Critique and Expertise Model. Since 2011, when the emergency nursing master's program was opened, 26 people enrolled in the program and seven instructors who taught in the program constituted the research group. Due to the different locations of the participants and the researcher and the Covid-19 outbreak, interviews with 12 students and two nurse educators were conducted on the online platform (Zoom/Google Classroom) between 2020-2021. Data were collected using a semi-structured interview form and analyzed using thematic content analysis. Results: The majority of the students who participated in the study (n=10) were female and their ages ranged between 25 and 40. No sociodemographic information was provided as the identity of the faculty members could be revealed. As a result of the content analysis, 10 main themes and 23 sub-themes were identified. The themes related to “Goals and Objectives” and “Future of the Program” were found to be prominent. Conclusion: The Emergency Nursing Master's Program responds to an important need by filling the lack of basic courses in the field of emergency in the undergraduate nursing curriculum in Turkey. Although faculty members and students are satisfied with the general structure of the program, they expect the reflections of the diploma in the professional field to be clearly determined.

Amaç: Bu çalışmada, Türkiye’deki bir üniversitenin Acil Hemşireliği Yüksek Lisans Programını öğrenciler ve hemşire eğitimci görüşleri doğrultusunda değerlendirmek amaçlandı. Yöntem: Bu çalışma, Eisner Eğitsel Eleştiri ve Uzmanlık Modeli'ni kullanan nitel yaklaşımlı bir program değerlendirme çalışmasıdır. Acil hemşireliği yüksek lisans programının açıldığı 2011 yılından bugüne kadar, programa kayıt olan 26 kişi ve programda ders veren yedi eğitici, araştırmanın örneklemini oluşturdu. Katılımcıların ve araştırmacının farklı şehirlerde ikamet etmesi ve COVID-19 salgını nedeniyle 12 öğrenci ve iki hemşire eğitimci ile görüşmeler çevrimiçi platform (Zoom/Google Classroom) üzerinden 2020-2021 tarihleri arasında gerçekleştirildi. Veriler yarı yapılandırılmış görüşme formu ile toplandı ve içerik analizi ile çözümlendi. Bulgular: Öğrencilerin çoğunluğu (n=10) kadın olup, yaşları 25 ile 40 arasında değişmektedir. Eğiticilerin kimliği açığa çıkabileceği için herhangi bir sosyodemografik bilgi verilmedi. Yapılan içerik analiz sonucunda, 10 ana tema ve 23 alt tema belirlendi. “Amaç ve Hedefler” ile “Programın Geleceği” ne ilişkin temaların ön plana çıktığı saptandı. Sonuç: Acil Hemşireliği Yüksek Lisans Programı, Türkiye'deki hemşirelik lisans müfredatında acil alanına yönelik temel derslerin eksikliğini kapatarak önemli bir ihtiyaca yanıt vermektedir. Öğretim üyeleri ve öğrenciler, programın genel yapısından memnun olmakla birlikte, diplomanın mesleki alandaki yansımalarının net bir şekilde belirlenmesini beklemektedir.
Acil Hemşireliği Yüksek Lisans Programının Eisner Modeli Çerçevesinde Eğitsel Eleştirisi: Nitel Araştırma
Keywords: Emergency Nursing; Acil Servis Hemşireliği